The Impact of United Nations Peacekeeping Missions on Conflict Resolution in Sub-Saharan Africa - Ojo-Lanre, Temiloluwa Anne Ojo-Lanre; Amodu, Akeem Amodu (African Journal of Stability and Development (AJSD), 2025)
The persistent prevalence of armed conflicts in Sub-Saharan Africa has necessitated the continuous deployment of United Nations (UN) peacekeeping missions aimed at maintaining peace and facilitating post-conflict recovery. Despite these efforts, the region remains plagued by violence, state fragility, and recurring crises, raising critical questions about the actual impact of UN peacekeeping missions on conflict resolution. This study investigates the effectiveness of UN peacekeeping operations in resolving conflicts and fostering sustainable peace in Sub-Saharan Africa. Anchored in liberal institutionalism and conflict transformation theory, the research assesses the extent to which UN interventions have achieved their intended goals. Employing a qualitative, case study approach, the study draws on secondary data from UN reports, academic literature, and policy analyses. It examines four key missions: MONUC/MONUSCO in the Democratic Republic of Congo, UNMISS in South Sudan, MINUSMA in Mali, and MINUSCA in the Central African Republic. The findings reveal mixed outcomes: while the missions have contributed to civilian protection, humanitarian support, and the reduction of open hostilities, they have often fallen short in addressing the root causes of conflict, facilitating political reconciliation, and achieving long-term peace. Key challenges identified include mandate ambiguity, limited resources, lack of local ownership, and complex political environments. The study concludes that while UN peacekeeping missions play a critical role in stabilising conflict zones, their effectiveness in achieving comprehensive conflict resolution remains constrained by operational, structural, and political limitations. To enhance their impact, the study recommends clearer mandates, stronger collaboration with regional organisations such as the African Union, greater investment in peacebuilding, and increased inclusion of local actors in the peace process. The paper contributes to ongoing debates on global peacekeeping practices and offers insights for policymakers and international actors involved in African conflict resolution.